2022
DOI: 10.1186/s40529-022-00346-9
|View full text |Cite
|
Sign up to set email alerts
|

Fungi associated with the potato taste defect in coffee beans from Rwanda

Abstract: Background Potato taste defect (PTD) of coffee is characterized by a raw potato like smell that leads to a lower quality taste in the brewed coffee, and harms the commercial value of some East African coffees. Although several causes for PTD have been proposed, none of them have been confirmed. Recently, high throughput sequencing techniques and bioinformatic analysis have shown great potential for identifying putative causal agents of plant diseases. Toward the goal of determining the cause of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The presence of these analytes can potentially elucidate the biochemical mechanism linking antestia bug damage to PTD. For example, one potential pathway is that bug damage to the coffee plant creates favorable conditions for microorganisms, with research highlighting that bacteria and fungi found on PTD-affected coffee beans produced IPMP as a metabolite [12][13][14]. Previous research has shown that the presence of microorganisms on coffee beans can cause the concentration of various compound classes like hydrocarbons, phenols, ketones, and aldehydes in coffee to increase [3,63,64].…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…The presence of these analytes can potentially elucidate the biochemical mechanism linking antestia bug damage to PTD. For example, one potential pathway is that bug damage to the coffee plant creates favorable conditions for microorganisms, with research highlighting that bacteria and fungi found on PTD-affected coffee beans produced IPMP as a metabolite [12][13][14]. Previous research has shown that the presence of microorganisms on coffee beans can cause the concentration of various compound classes like hydrocarbons, phenols, ketones, and aldehydes in coffee to increase [3,63,64].…”
Section: Tablementioning
confidence: 99%
“…However, the mechanism linking coffee plant damage from the antestia bug to the presence of IPMP in volatile headspace of affected beans remains unclear, especially since PTD can be present in coffee beans with and without visual insect damage [9]. It has been hypothesized that damage from the bug either provides favorable growth conditions for microorganisms that can produce IPMP [12][13][14] or initiates the conversion of hydroxypyrazines naturally produced by the plant into methoxypyrazines like IPMP via O-methyltransferase expression [15].…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, coffee beans are often dried suboptimally due to high rainfall, erratic weather, and humidity in highland areas [28 , 29 , 30] . Traditional drying of coffee beans in direct sunshine with or without a base in the open air encourages the growth of 10 to 13 varieties of fungus [31 , 32] .…”
Section: Introductionmentioning
confidence: 99%
“…Penicillium cvjetkovicii belongs to the slow-growing subgenus Aspergilloides , section Cinnamopurpurea , series Idahoensia (Houbraken et al 2020 ). Species from this section have been found as contaminants on food products, such as P. fluviserpens isolated from tomato fruit (Nguyen et al 2020 ), P. cinnamopurpureum and P. malacaense reported from meju samples in Korea (Jung et al 2012 ; Kim et al 2015 ), and P. cinnamopurpureum contributing to the potato-taste-defect of coffee (Hale et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%